Furniture Manufacturing A Production Engineering Approach - Ratnasingam, Jegatheswaran; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This volume covers all aspects of furniture manufacturing from a production engineering perspective. It takes a step-by-step pedagogical approach, dwelling on details which must be understood at every process, as the furniture makes its way through the factory shop floor. The content highlights the global industry, and discusses furniture design and manufacturing systems. The chapters also discuss every stage of the manufacturing process until the finished product is packaged. There is also emphasis on strength design of furniture, furniture testing, environmental compliance, and automation. The contents also discuss the optimization of furniture manufacturing through a mathematical approach and highlights the current global trends impacting the furniture manufacturing industry, especially the circular economy and Industry 4.0. This volume will a useful resource to those in academia and industry.
The furniture manufacturing industry -- Furniture Design and Innovation -- Furniture Manufacturing Systems -- Production Flow In Furniture Manufacturing -- Preparing The Furniture Parts -- Joints In Furniture.
Keywords: Industrial engineering; Production engineering; Engineering design; Industrial and Production Engineering; Engineering Design; Process Engineering; Furniture industry and trade; Production engineering